Structural determination and chemical esterification of the sophorolipids produced by Candida bombicola grown on glucose and alpha-linolenic acid - Gupta, Reetika; Prabhune, Asmita (Biotechnology Letters, 2012)
The extracellular surface-active glycolipids produced by the yeast, Candida bombicola when grown on glucose and alpha-linolenic acid, were analyzed by HPLC with electro-spray ionization (ESI-MS) and collision-induced dissociation mass spectrometry. The analysis confirmed that the sophorolipid (SL) mixture contained three different forms of C18:3 SL molecules: free acid, lactone and a diacetylated lactone, which has not been reported previously. Also a minor amount of diacetylated lactone form of C18:1 SL was detected. Further, the SL mixture was subjected to chemical esterification reaction with sodium methoxide. The reaction product was analyzed with ESI-MS and confirmed to be the single homogenous esterified product containing C18:3 moieties in its fatty acid chain.
Keywords: Candida bombicola; Collision-induced dissociation mass spectrometry; Electrospray ionization mass spectrometry; HPLC; Linolenic acid; Sophorolipid methyl ester